Cryptographic Hashing Method using for Secure and Similarity Detection in Distributed Cloud Data - A. Mohamed Divan Masood; S. K. Muthusundar (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The explosive increase of data brings new challenges to the data storage and supervision in cloud settings. These data typically have to be processed in an appropriate fashion in the cloud. Thus, any improved latency may originanimmense loss to the enterprises. Duplication detection plays a very main role in data management. Data deduplication calculates an exclusive fingerprint for each data chunk by using hash algorithms such as MD5 and SHA-1. The designed fingerprint is then comparing against other accessible chunks in a database that dedicates for storing the chunks. As an outcome, Deduplication system improves storage consumption while reducing reliability. Besides, the face of privacy for responsive data also arises while they are outsourced by users to cloud. Aiming to deal with the above security challenges, this paper makes the first effort to honor the notion of distributed dependable Deduplication system. We offer new distributed Deduplication systems with privileged reliability in which the data chunks are distributed across a variety of cloud servers. The protection needs an different of using convergent encryption as in foregoing Deduplication systems.